If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 3h + -5 Reorder the terms: 4 = -5 + 3h Solving 4 = -5 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 4 + -3h = -5 + 3h + -3h Combine like terms: 3h + -3h = 0 4 + -3h = -5 + 0 4 + -3h = -5 Add '-4' to each side of the equation. 4 + -4 + -3h = -5 + -4 Combine like terms: 4 + -4 = 0 0 + -3h = -5 + -4 -3h = -5 + -4 Combine like terms: -5 + -4 = -9 -3h = -9 Divide each side by '-3'. h = 3 Simplifying h = 3
| 4.8+1.6n=0.64 | | in22/in4 | | Ax=15+bc | | -136=8n | | 3cos(6x)-8cos(3x)+5=0 | | 9x-6(x+2)-6=12x | | 9=2w+3 | | y=x+35-21 | | 0=2x^2+3x-8 | | X=(4-1) | | 0=v-3 | | halfx+4=17 | | 2x^2-20y+42=0 | | 1.5x=150x | | -3x+1=2x-3 | | (5x-6)^(1/3) | | -3x+1=-2x-3 | | x+0.85x+(0.85x+12)=180 | | 450=100ekt | | 64-40ab=0 | | -120=-12n | | 4sinx-2=2 | | 6k-4=18 | | 6/3*2a | | 0.5h+8.7=12.35 | | 84=14p | | 5(3-4x)-2(x-3)= | | x*1.4=1000000 | | 1/5s=125=2,225 | | 5x+10-2x-3x+2+4x=1 | | 9x(9x-4)=0 | | 3D-2c=-17 |